The Economic Impact of Natural Disasters in Pacific Island Countries : Adaptation and Preparedness - Lee, Dongyeol (IMF Working Papers; Working Paper ;, 2018)
Pacific island countries are highly vulnerable to various natural disasters which are destructive, unpredictable and occur frequently. The frequency and scale of these shocks heightens the importance of medium-term economic and fiscal planning to minimize the adverse impact of disasters on economic development. This paper identifies the intensity of natural disasters for each country in the Pacific based on the distribution of damage and population affected by disasters, and estimates the impact of disasters on economic growth and international trade using a panel regression. The results show that 'severe' disasters have a significant and negative impact on economic growth and lead to a deterioration of the fiscal and trade balance. We also find that the negative impact on growth is stronger for more intense disasters. Going further this paper proposes a simple and consistent method to adjust IMF staff's economic projections and debt sustainability analysis for disaster shocks for the Pacific islands. Better incorporating the economic impact of natural disasters in the medium- and long-term economic planning would help policy makers improve fiscal policy decisions and to be better adapted and prepared for natural disasters.